Case report: A novel surgical technique for rapid valve-in-ring implantation into the native aortic annulus during left ventricular assist device implantation - Pya, Yuriy; Mussayev, Abdurashid; Novikova, Svetlana; Bekbossynova, Makhabbat; Alimbayev, Serik; Khissamutdinov, Nail; Kapyshev, Timur; Kuanyshbek, Aidyn; Lesbekov, Timur (Frontiers in Cardiovascular Medicine, 2023)
The implantation of a left ventricular assist device (LVAD) has become an essential requirement for managing patients with end-stage heart failure. However, aortic valve insufficiency is a contraindication for LVAD implantation in patients with end-stage heart failure, partly because of the decreasing efficiency of mechanical circulatory support and the eventual development of right ventricular failure. Herein, we present the first case of performing transcatheter aortic valve replacement in valve-in-ring along with LVAD implantation for the treatment of a 60-year-old male suffering from refractory heart failure due to dilated cardiomyopathy and pure aortic insufficiency in need of a new aortic bioprosthesis. A balloon-expandable bioprosthetic transcatheter heart valve was implanted into a previously sewn annulus ring into the aortic root via transaortic access. Subsequently, a centrifugal-flow LVAD was implanted. Postoperatively, the patient was in New York Heart Association Functional Class (NYHA) II with 6-min walk test of 310 m. The patient has completed 6 months of follow-up with no events. This novel and feasible surgical technique reduced the cardiopulmonary bypass time and duration of surgery. Furthermore, it avoids the risk of redo sternotomy and decreases the chances of paravalvular leakage and worsening of aortic regurgitation.